1986
DOI: 10.1161/01.res.59.6.597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hereditary Syrian hamster cardiomyopathy by 31P nuclear magnetic resonance spectroscopy: improvement after acute verapamil therapy.

Abstract: The relation between metabolic and functional derangement in various cardiomyopathies has not been well characterized. This information was specifically sought in a spontaneous cardiomyopathic model. Metabolic and hemodynamic parameters were obtained in glucose-perfused beating hearts of 180-200-day-old cardiomyopathic Syrian hamsters and age-matched healthy animals. This period in the cardiomyopathic hamster lifetime is intermediary between the necrotic phase and the appearance of heart failure. We used 31P n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…A recent study by Sanbe et al (29) examined high-energy phosphate stores in residual intact myocardium of rat hearts with infarct sizes similar to our work using a columnfreezing method. In agreement with our results, these authors found significant reductions of CP and creatine [1][2][3][4][5][6][7][8][9][10][11][12] wk after MI. In contrast, however, they also found significant reductions of ATP and of Pi.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A recent study by Sanbe et al (29) examined high-energy phosphate stores in residual intact myocardium of rat hearts with infarct sizes similar to our work using a columnfreezing method. In agreement with our results, these authors found significant reductions of CP and creatine [1][2][3][4][5][6][7][8][9][10][11][12] wk after MI. In contrast, however, they also found significant reductions of ATP and of Pi.…”
Section: Discussionsupporting
confidence: 92%
“…These results show that myocytes in the noninfarcted region do not maintain normal levels of creatine. Reduced creatine and CP levels are characteristic of many models of chronic cardiac injury (6)(7)(8)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20 % increase in MVO2 during hypoglycemia was due to an increase in pressure-work. A sufficient myocardial energy supply under this condition can be assumed because of a) an unchanged myocardial contractile function, b) constant high energy phosphate levels, and c) a constant mitochondrial activity, as estimated by the PCr/Pi ratio (20).…”
Section: Discussionmentioning
confidence: 99%
“…31P MR spectra of the beating heart were obtained on a vertical 5.6-T 76-mm-bore spectrometer as described earlier (14). 31P MR spectra were obtained without proton decoupling at 97.3 MHz.…”
Section: P Mr Spectroscopymentioning
confidence: 99%